2011
DOI: 10.3109/10428194.2011.591004
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma cell adhesion to bone marrow stromal cells confers drug resistance by microRNA-21 up-regulation

Abstract: The bone marrow microenvironment plays a role in myeloma cell proliferation and adhesion-mediated drug resistance. In this study, we investigated microRNA-21 (miR-21) expression changes in myeloma cells that adhered to bone marrow stromal cells (BMSCs). In addition, we studied the synergistic effect of miR-21 inhibition with dexamethasone (Dex), doxorubicin (Dox), or bortezomib (Bort) on myeloma cell survival. We found that up-regulation of miR-21 expression was partially driven by nuclear factor-κB (NF-κB) si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 37 publications
(46 reference statements)
5
73
1
Order By: Relevance
“…Study of Wang et al and Zang et al showed bone marrow stromal cells (BMSCs) regulate the drug sensitivity of myeloma cells through the inhibited expression of miRNA and IL-6 plays a pivotal role in the occurrence of drug resistance [42,43]. IGF-1 produced by plasma cells, as well as by the marrow microenvironment, is a critical mediator of a number of downstream effects that contribute to multiple myeloma pathobiology.…”
Section: Introductionmentioning
confidence: 99%
“…Study of Wang et al and Zang et al showed bone marrow stromal cells (BMSCs) regulate the drug sensitivity of myeloma cells through the inhibited expression of miRNA and IL-6 plays a pivotal role in the occurrence of drug resistance [42,43]. IGF-1 produced by plasma cells, as well as by the marrow microenvironment, is a critical mediator of a number of downstream effects that contribute to multiple myeloma pathobiology.…”
Section: Introductionmentioning
confidence: 99%
“…The reactivation of tumor suppressor miRNAs, such as miR-29b or miRNA-30-5p, in myeloma cells, has therapeutic effects (40,41). On the other hand, miR-21 has been demonstrated to have an oncogenic feature (42). We proved that inhibition of the miR-21 halts the progression of multiple myeloma (MM) (43).…”
Section: Microrna As Therapeutic Targetmentioning
confidence: 81%
“…In addition, the increase of serum miR-142-5p, miR-660 and miR-29a in MM patients were also been validated, of which, miR-29a proved its potent role in discriminating MM sera from healthy controls [29]. Since miR-21 was found to be related with malignant characteristic including tumorigenesis, invasion, and apoptosis resistance, another report from Wang et al also revealed that circulating miR-21 expression level was significantly upregulated in patients with MM and involved in progression of MM [30].…”
Section: Circulating Mirnas In Hematological Malignanciesmentioning
confidence: 96%